The Degree-Based Topological Indices for Two Special Families of Graphs of Diameter Three - Khalid, Aqsa; Kausar, Nasreen; Munir, Mohammad; Aydi, Hassen; Kousar, Sajida; Gaba, Yae Ulrich (WILEY, 2021)
In this research article, we determine some vertex degree-based topological indices or descriptors of two families of graphs, i.e., G=C-4(K-n) and G=C-4(K-n)+v(1)v(3), where C-4(K-n) is a graph obtained by identifying one of the vertices of K-n with one vertex of C-4. Similarly, a graph formed by joining one of the vertices of K-n with one vertex of C-4+v(1)v(3) is known as the C-4(K-n)+v(1)v(3) graph.
Keywords: SUM-CONNECTIVITY INDEX; HARMONIC INDEX; Physics